Case Report: Unilateral Secondary Spontaneous Pneumothorax caused by Pulmonary Tuberculosis in a Heavy Smoker - Syazili Mustofa; Antoni Antoni (Sriwijaya Journal of Medicine, 2023)
Pneumothorax is an accumulation of air between the lungs and the chest wall that can occur either spontaneously or in conjunction with an underlying lung disease (primary spontaneous pneumothorax; secondary spontaneous pneumothorax, respectively). The primary manifestations of this ailment are chest discomfort and dyspnea. Secondary spontaneous pneumothorax is a common and potentially life-threatening consequence of pulmonary tuberculosis (TB) that frequently occurs in clinical settings and requires prompt and effective treatment. This case report seeks to comprehend the underlying mechanisms of spontaneous pneumothorax resulting from tuberculosis and effectively diagnose and treat this condition. A 37-year-old male presented to the emergency department at Abdoel Moeloek Regional General Hospital in Lampung Province with worsening dyspnea, followed by coughing and right-sided chest pain. By doing a thorough analysis of the patient's medical history, performing a physical examination, and conducting other tests, it was determined that the patient is suffering from a right secondary spontaneous pneumothorax, which is a result of pulmonary tuberculosis. The patient had WSD installation management and thereafter received hospitalization for symptomatic therapy and antibiotic treatment.